Proposition 99, The Cigarette And Tobacco, Tax Initiative, Its Promoters Are Trying To Slip One By You (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Copy; Marginalia; Three different clippings regarding California Proposition 99: an ad headline, a copy of ballot and a list of 6 'facts' on Proposition 99. Highlights that the ballot initiative does not specifically earmark cigarette tax income for smoking-related programs. Argues against Proposition 99 as regressive, crime-promoting, restrictive of civil liberties, and a loophole in the California spending cap.